1999
DOI: 10.1046/j.1460-9568.1999.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of reward circuitry in human opiate addicts

Abstract: The neurobiological mechanisms of opiate addictive behaviour in humans are unknown. A proposed model of addiction implicates ascending brainstem neuromodulatory systems, particularly dopamine. Using functional neuroimaging, we assessed the neural response to heroin and heroin-related cues in established opiate addicts. We show that the effect of both heroin and heroin-related visual cues are maximally expressed in the sites of origin of ascending midbrain neuromodulatory systems. These context-specific midbrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
55
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(66 citation statements)
references
References 42 publications
10
55
0
1
Order By: Relevance
“…It is methodologically difficult if not impossible to eliminate this problem, and the observed pattern therefore remains ambiguous; however, there is clearly no support here for the alternative view that abstinence actually heightens cue reactivity by enhancing cue salience. The present findings are consistent with other reports that prior nicotine administration sensitizes subjective responses to cocaine-related cues (e.g., Reid et al 1998) and that heroin addicts show greater relative activation of prefrontal cortex and amygdala during exposure to heroin-related cues immediately following administration (under double-blind conditions) of an intravenous dose of heroin rather than placebo (Sell et al 1999).…”
Section: Discussionsupporting
confidence: 92%
“…It is methodologically difficult if not impossible to eliminate this problem, and the observed pattern therefore remains ambiguous; however, there is clearly no support here for the alternative view that abstinence actually heightens cue reactivity by enhancing cue salience. The present findings are consistent with other reports that prior nicotine administration sensitizes subjective responses to cocaine-related cues (e.g., Reid et al 1998) and that heroin addicts show greater relative activation of prefrontal cortex and amygdala during exposure to heroin-related cues immediately following administration (under double-blind conditions) of an intravenous dose of heroin rather than placebo (Sell et al 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Subsequent studies noted cerebellar activity during cocaine craving (Kilts et al, 2001;Bonson et al, 2002), during recall or imagery of cocaine-use experiences (Wang et al, 1999;Kilts et al, 2001), and during stimulant expectancy (Volkow et al, 2003). Acute administration of or cues for other stimulants or psychoactive drugs also has been associated with increased cerebellar activity (Volkow et al, 1996(Volkow et al, , 1988London et al, 1990;Ghatan et al, 1998;Sell et al, 1999;Domino et al, 2000). Two studies reported cerebellar midline (vermis) activation by alcohol odor cues and by stimulant expectancy (Schneider et al, 2001;Volkow et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Intense craving for the drug is a fundamental feature of addiction and is thought to trigger drug use and relapse. Environmental cues associated with drug taking behavior are potent stimulators of opiate craving in humans (Childress et al, 1986;Sell et al, 1999). A better understanding of brain mechanisms involved in producing drug craving would lead to better treatments for drug addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Human brain imaging studies have shown that drugassociated cues strongly activate the anterior cingulate cortex (Cg), the amygdala and other basal forebrain regions (Childress et al, 1999;Sell et al, 1999). Environments associated with drug taking can strongly motivate drugseeking behavior in human addicts (Childress et al, 1986;Wallace, 1989) and the conditioned place preference (CPP) paradigm is an animal model of this type of cue-elicited conditioning (Bardo et al, 1995;Tzschentke, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation